Safety and efficacy of oral administrated cepharanthine in non-hospitalized, asymptomatic or mild COVID-19 patients: a Double-blind, randomized, placebo-controlled trial - Jianyi Wei; Shupeng Liu; Yuexiang Bian; Lei Li; Biyun Qian; Zixuan Shen; Yan Zhang; Adila Abuduaini; Fuchen Dong; Xin Zhang; Jinhui Li; Yongpei Yu; et al. (Scientific Reports)
Abstract Cepharanthine (CEP) is a natural remedy that potently inhibits SARS-CoV-2 activity both in vitro and in vivo. To evaluate the efficacy and safety of CEP compared with placebo in adults with asymptomatic or mild coronavirus disease 2019 (COVID-19), we conducted a proof-of-concept, double-blind, randomized, placebo-controlled trial. Patients were randomized to receive 120 mg/day of CEP, 60 mg/day CEP or placebo for 5 days. Main outcome was the time from randomization to negative nasopharyngeal swab and safety. Among 262 randomized participants, 188 completed the trial among group of 120 mg/day CEP (n = 65), 60 mg/day CEP (n = 68) and placebo (n = 55). Neither 120 mg/day or 60 mg/day CEP shortened the time to negative significantly compared with placebo. However, 60 mg/day CEP showed a slight trend (difference=-0.77 days, hazard ratio (HR) = 1.40, 95% CI 0.97–2.01, p = 0.072). In analysis of participants with good medication compliance, 60 mg/day CEP significantly shortened the time to negative (difference=-0.87 days, HR = 1.56, 95% CI 1.03–2.37, p = 0.035). Adverse events were not different among the three groups, and no serious adverse events occurred. In conclusion, treatment of asymptomatic or mild Covid-19 with 120 mg/day or 60 mg/day did not shorten the time to negative significantly. However, 60 mg/day CEP showed a slight trend which needs future confirmatory trials to validate. (NCT05398705).